Kathā Hīra Rāñjhani kī - Gurdas Guni (Bhāshā Vibhāga, Pañjāba, 1972)
Narrative poem about the 15th century Punjabi lovers Hir and Ranjha; in Braj, dialect of Hindi, with introduction and footnotes in Hindi.